Mechanistic basis of oxygen sensitivity in titanium - Chong, Yan; Poschmann, Max; Zhang, Ruopeng; Zhao, Shiteng; Hooshmand, Mohammad S.; Rothchild, Eric; Olmsted, David L.; Morris, J. W.; Chrzan, Daryl C.; Asta, Mark; Minor, Andrew M. (Science advances, 2020)
A systematic study of Ti-O alloys reveals the mechanism behind acute oxygen sensitivity in titanium. One of the most potent examples of interstitial solute strengthening in metal alloys is the extreme sensitivity of titanium to small amounts of oxygen. Unfortunately, these small amounts of oxygen also lead to a markedly decreased ductility, which in turn drives the increased cost to purify titanium to avoid this oxygen poisoning effect. Here, we report a systematic study on the oxygen sensitivity of titanium that provides a clear mechanistic view of how oxygen impurities affect the mechanical properties of titanium. The increased slip planarity of Ti-O alloys is caused by an interstitial shuffling mechanism, which is sensitive to temperature, strain rate, and oxygen content and leads to the subsequent alteration of deformation twinning behavior. The insights from our experimental and computational work provide a rationale for the design of titanium alloys with increased tolerance to variations in interstitial content, with notable implications for more widespread use of titanium alloys.